Strategi Pengembangan Kemampuan Sosial Emosional Anak Usia Dini dengan Pembudayaan Antri - Rahayu, Fitri; Arkam, Rohmad; Mustikasari, Rizki (MENTARI: Jurnal Pendidikan Anak Usia Dini, 2023)
One aspect of early childhood development that needs to be developed is the social emotional aspect. The way to develop the social emotional aspect is to apply the habit of queuing culture. The aim of the research is to find out the strategies and results of children’s social emotional development related to getting used to the culture of queuing. The data sources in this research were the principal, class A teacher, and class A children at Dharma Wanita Dukuh Kindergarten. The method used in this research is descriptive qualitative. The techniques used in data collection are observation, interviews and documentation. The research data shows that the strategy development strategy was carried out by queuing children when washing their hands after activities that involved washing hands by lining up at the back waiting for their turn. The results of developing children’s social emotional abilities by getting used to the culture of queuing show effective results.